Energy Harvesting and Storage: Materials, Devices, and Applications XIII 2023
DOI: 10.1117/12.2672550
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things (IoT) in solar energy: a bibliometrics analysis and global publications trends

Maryam AlMallahi,
Wafaa Al Nassan,
Khaled Obaideen
et al.

Abstract: With the modernization of cities, the concept of the Internet of Things (IoT) is gaining popularity and becoming a vital source of smart developments. An added advantage of solar energy systems, IoT applications enable automatic and remote sensing, processing, and execution. IoT ensures that information is easily available and accessible from any location around the world. The IoT applications improve the visibility, scalability, and cost-effectiveness of solar energy generation and service. A bibliometric ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Reference source not found., this research uses a systematic and detailed approach to understand the role of radar technology in the health care sector, and more specifically in the area of aging and elderly care. Our research methodology is underpinned by a dual-framework: a thorough literature study along with an in-depth bibliometric analysis [37][38][39][40][41]. This method includes data acquisition from the principal academic databases including Scopus, using bibliometric visualization app like VOSviewer.…”
Section: Methodsmentioning
confidence: 99%
“…Reference source not found., this research uses a systematic and detailed approach to understand the role of radar technology in the health care sector, and more specifically in the area of aging and elderly care. Our research methodology is underpinned by a dual-framework: a thorough literature study along with an in-depth bibliometric analysis [37][38][39][40][41]. This method includes data acquisition from the principal academic databases including Scopus, using bibliometric visualization app like VOSviewer.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of this research, visualized in Error! Reference source not found., incorporates the state-of-the-art methods aimed for a thorough bibliometric [96][97][98][99][100][101] and text mining survey of the Kalman Filter application in the contemporary agriculture, with the emphasis on advanced crop monitoring. This strategy is carefully tailored to provide quantitative as well as qualitative contributions associated with the critical role of the Kalman Filter technology and its improvements in the agricultural sector.…”
Section: Methodsmentioning
confidence: 99%
“…As we can see in Figure 1, the implementation of holistic bibliometric techniques in this research is intended to capture the scope of the ongoing applications of cryo-cooling technologies into current spectroscopy research, with data practically from the commonly relied databases such as Scopus [28][29][30][31]. Within our search strategy, we apply a set of exactly defined keywords together with Boolean operators dealing directly with working techniques of SC sources or more generallywith the spectroscopy -which helps to select the most relevant sources and form a dataset that encompasses both classical and ground breaking studies in the field.…”
Section: Methodsmentioning
confidence: 99%